2009
DOI: 10.1007/s10620-009-1012-0
|View full text |Cite
|
Sign up to set email alerts
|

Methane and the Gastrointestinal Tract

Abstract: This review of the literature discusses the significance of enteric flora, the biogenesis of methane, and its clinical associations. Furthermore, we examine the evidence for an active role of methane in gastrointestinal motility and the potential applications to future therapeutics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
143
2
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 198 publications
(152 citation statements)
references
References 57 publications
3
143
2
4
Order By: Relevance
“…For example, it is possible that methanogens may favor the slow-transit environment, a hypothesis supported by studies indicating that treatment with laxatives and bowel cleansing can reduce or eliminate methane production in some patients ( 14 ). As noted earlier, methanogens exist within a complex web of syntrophic and competitive relationships; thus, it is possible that methanogens could alter transit indirectly as a refl ection of competition for hydrogen and the relative numbers of methanogens vs. sulfate-reducing bacteria ( 14 ).…”
Section: Is There a Role For Methane In Constipation-predominant Irrimentioning
confidence: 94%
See 2 more Smart Citations
“…For example, it is possible that methanogens may favor the slow-transit environment, a hypothesis supported by studies indicating that treatment with laxatives and bowel cleansing can reduce or eliminate methane production in some patients ( 14 ). As noted earlier, methanogens exist within a complex web of syntrophic and competitive relationships; thus, it is possible that methanogens could alter transit indirectly as a refl ection of competition for hydrogen and the relative numbers of methanogens vs. sulfate-reducing bacteria ( 14 ).…”
Section: Is There a Role For Methane In Constipation-predominant Irrimentioning
confidence: 94%
“…Th e fermentation of fi ber also produces formate, carbon dioxide, and hydrogen gas ( 13 ). Th e hydrogen gas produced during fermentation is eliminated through three pathways: (i) via fl atus; (ii) absorption into the systemic circulation and respiratory excretion; and (iii) metabolism by the colonic microbiota, which is considered to be the major source of hydrogen disposal ( 14 ).…”
Section: Methane and Methanogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of exogenous CH 4 on animal pathophysiology indicate the possibility of endogenous CH 4 production. The studies of CH 4 generation by humans have suggested that CH 4 may be positively linked to the pathophysiology of gut disorders, including colon cancer, diverticulosis, inflammatory bowel disease and irritable bowel syndrome (Costello et al, 2013;Roccarina et al, 2010;Sahakian et al, 2010), but generally, the relationship between CH 4 and age has not been adequately explored in these studies. Polag et al (2014) demonstrated that the percentage of breath CH 4 producers increase linearly with age and suggested that this agecorrelation should be considered when investigating the relationship between CH 4 generation and specific diseases.…”
Section: Uncertainties and Limitationsmentioning
confidence: 99%
“…A major source of both gas (methane and hydrogen sulfide) and ammonia is intestinal microbiota (Sahakian et al. 2010; Dhiman 2013), which suggests the change in microbial population induced by TU‐100 treatment may be involved in the mechanism of action of the medicine. Research cited on TU‐100 has focused on intestinal tract effects as historically these are the symptoms for which the TU‐100 formulation was used.…”
Section: Introductionmentioning
confidence: 99%